Parekan Buduh Dalam Pementasan Drama Gong Bali (Perspektif Estetika Humor) - Pratama, I Gede Bagus Wira; Nerawati, Ni Gusti Ayu Agung; Piartha, I Nyoman (Widya Sandhi, 2024)
The structural form of a gong drama performance is always associated with the musical accompaniment to the performance, namely percussion petegak, pepeson, pasiatan, and finally pamuput. Followed by the Prologue, which is a panyembrama or introductory words at the start of a drama play, then it starts with Pepeson which is a sign of the appearance of a person or several characters in starting scene by scene in each act. There are pepeson scenes for petangkilan, meseneng-senengan scenes, romance scenes, pasiatan scenes, and pamuput scenes. However, according to the sources who have explained above, the structure of the gong drama performance is uncertain depending on the story being told but still maintains the standard of Balinese gong drama. The characteristics of the punakawan buduh in the Balinese gong drama performance can be divided into two characters, where there is a tough character which characterizes the human nature of being arrogant, arrogant, self-righteous and fierce. There are also soft characters that are inversely proportional to hard characters, soft characters emphasize human traits that are kind, full of empathy, intelligent, and not arrogant. These two characters symbolize different dualities or what is called rwa bhineda, traits that cannot be separated in human traits in general. The aesthetic theory of humor contained in Punakawan Buduh is divided into three parts, the first is the theory of superiority, the second is the theory of incompatibility and the third is the theory of tension. However, during the performance, the Punakawan Buduh characters, without realizing it, were using this third theory when conveying the joke material. Because in general the Punakawan Buduh characters often practice on stage without knowing the theory of humor they are using, but each joke material already contains this theory of humor according to the situation that occurs during the performance of the Balinese gong drama